Pengaruh Insentif, Lingkungan Kerja, Disiplin Kerja dan Pelatihan Kerja Terhadap Kinerja Karyawan Di PT.Trisakti Purwosari Makmur Pasuruan - Usiaman, Aldi; Rizal, Mohammad; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine "the influence of incentives, work environment, work discipline, and work training on employee performance at PT Trisakti Purwosari Makmur Pasuruan". This research uses quantitative research methods using a questionnaire with a 1-5 Likert scale. The population in this study were all secondary department employees of PT Trisakti Purwosari Makmur. The sampling method used was saturated sampling, with a total of 82 respondents. Data analysis was carried out using research instrument tests, classical assumption tests, multiple linear regression analysis tests, hypothesis tests and coefficient of determination tests. The collected data was analyzed using IBM SPSS Statistics software. The results of simultaneous testing of the influence of incentives, work environment, work discipline and work training have a positive and significant influence on employee performance. The results of partial testing indicate that incentives, work discipline and work training have an effect on employee performance, while the work environment does not have an effect on employee performance. Keywords: Incentives, Work Environment, Work Discipline, Job Training, Employee Performance